The Effect of Bay Leaves (Syzygium Polyanthum) Administration Towards the Final Weight and Carcass Percentage of Laserpuncture-Induced Male Hybrid Ducks - Lucia Tri Suwant (Journal of Global Pharma Technology, 2016)
The carcass weight of laserpuncture-induced male hybrid ducks is not maximum yet. Nevertheless, it can be resolved by using bay leaves (Syzygium polyanthum) as a supplementary feeding to support the optimal work of laserpuncture technology. This research aims to evaluate the impact of bay leaves (Syzygium polyanthum) towards final weight and carcass percentage of laserpuncture-induced male hybrid ducks. This research applied Completely Randomized Design (CRD) with three treatments. Each treatment consisted of six replications, and each replicate consisted of six male hybrid ducks with homogenous age and weight. The three treatments were P0 (Control), P1 (Laserpuncture), and P2 (Laserpuncture and bay leaves). The data were analyzed by using Analysis of Variance (ANOVA) and continued by Least Significant Difference (LSD). The results suggested that the bay leave administration on laserpuncture-induced male hybrid ducks (P2) provided a significant effect (P<0.05) in comparison with (P0) & (P1) on the final weight. However, an insignificant effect (P>0.05) was identified on the carcass percentage of male hybrid ducks. The bay leaves administration on laserpuncture-induced male hybrid ducks can intensify the final weight gained, but it does not affect the carcass percentage.Keywords: Hybrid Duck, Laserpuncture, Bay Leaves (Syzygium Polyanthum).